Peningkatan kemampuan pengendalian emosi dengan terapi kognitif perilaku pada klien skizofrenia paranoid - Farra Anisa Rahmania; Raden Ajeng Retno Kumolohadi (Universitas Muhammadiyah Malang, 2023)
Schizophrenia disorder is a disorder that causes the main symptoms, namely delusions, and hallucinations. In the patients in this study, the delusions that emerged were delusions of pursuit and delusions of grandeur. Meanwhile, the hallucinations that appear are auditory hallucinations such as noises, and visual hallucinations such as seeing supernatural beings. Patients also have difficulty controlling their emotions so they often get angry, say harsh things, and smash things. Patients find it difficult to do activities well in their social environment. The assessment was carried out using personality tests and intelligence tests. Based on the results of the assessment, the patient's diagnosis was schizophrenia with the paranoid type. The intervention given to patients is a cognitive behavioral therapy that focuses on controlling emotions. The results of interventions in patients show that cognitive behavioral therapy can help patients to be aware of their current condition, the will to control negative emotions, and the emergence of a desire to carry out activities such as looking for a job. The patient's family is given intervention including psychoeducation about the patient's condition, how to care for the patient, and how to support the patient. Gangguan skizofrenia merupakan gangguan yang menimbulkan gejala utama yaitu delusi, dan halusinasi. Pada pasien dalam penelitian ini, delusi yang muncul adalah delusi pengejaran dan delusi keagungan. Sedangkan halusinasi yang muncul adalah halusinasi pendengaran seperti suara bising, dan halusinasi visual seperti melihat makhluk gaib. Penderita juga sulit mengendalikan emosinya sehingga sering marah-marah, berkata kasar, dan membanting barang. Pasien merasa sulit untuk melakukan aktivitas dengan baik di lingkungan sosialnya. Penilaian dilakukan dengan menggunakan tes kepribadian dan tes inteligensi. Berdasarkan hasil asesmen, diagnosis pasien adalah skizofrenia dengan tipe paranoid. Intervensi yang diberikan kepada pasien adalah terapi perilaku kognitif yang berfokus pada pengendalian emosi. Hasil intervensi pada pasien menunjukkan bahwa terapi perilaku kognitif dapat membantu pasien untuk menyadari kondisinya saat ini, keinginan untuk mengendalikan emosi negatif, dan munculnya keinginan untuk melakukan aktivitas seperti mencari pekerjaan. Keluarga pasien diberikan intervensi diantaranya psikoedukasi tentang kondisi pasien, cara merawat pasien, dan cara support pasien.